Effect of individualized PEEP on lung ultrasound score and optic nerve sheath diameter in elderly patients undergoing laparoscopic rectal cancer surgery: A randomized controlled trial - Furong Bai; Hong Yin; Shuang Zhang; Daneng Wei; Jiansheng Wang; Mingliang Yi (PLoS ONE, 2025)
Objective Positive end-expiratory pressure (PEEP) is widely used during surgery, but its effects on lung and brain protection remain debated. This study aimed to evaluate the impact of individualized PEEP on lung ultrasound score (LUS) and optic nerve sheath diameter (ONSD) in elderly patients undergoing laparoscopic rectal cancer surgery. Methods Forty-six patients aged 60–79 years undergoing laparoscopic rectal tumour resection between June 2022 and December 2022 were randomized into two groups: Group E (individualized PEEP guided by driving pressure) and Group C (control group, PEEP = 5 cm H2O). LUS was assessed 30 minutes postoperatively. ONSD was measured at 5 minutes before anesthesia induction (T0), 5 minutes after tracheal tube insertion (T1), 5 and 60 minutes after Trendelenburg positioning (T2, T3), and 30 minutes postoperatively (T4). Arterial oxygen index (OI) and arterial partial pressure of carbon dioxide (PaCO2) were recorded post-intubation and pre-extubation. Postoperative pulmonary and neurological complications were followed up. Results Postoperative LUS was significantly lower in Group E than in Group C (P < 0.05). OI was significantly higher in Group E before extubation (P < 0.05). There were no significant differences in ONSD between groups. Within each group, ONSD values at T2 and T3 were significantly higher than those at T0 (P < 0.01). No significant differences were observed in the incidence of postoperative complications between the two groups. Conclusions During laparoscopic radical resection for rectal cancer, individualized PEEP reduces LUS scores, improves oxygenation, and does not increase ONSD values compared to fixed PEEP. Trial registration Chinese Clinical Trial Registry: ChiCTR2200060434.